2019
DOI: 10.3390/min9040202
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cement Hydration of Cemented Paste Backfill: DFT Study of Water Adsorption on Tricalcium Silicate (111) Surface

Abstract: Understanding cement hydration is of crucial importance for the application of cementitious materials, including cemented paste backfill. In this work, the adsorption of a single water molecule on an M3-C 3 S (111) surface is investigated using density functional theory (DFT) calculations. The adsorption energies for 14 starting geometries are calculated and the electronic properties of the reaction are analysed. Two adsorption mechanisms, molecular adsorption and dissociative adsorption, are observed and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
26
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 53 publications
9
26
1
Order By: Relevance
“…It is also worth noting that in addition to zeolites, calcium silicates also play an important role in the composition of Portland cement, and thus have significant environmental impact. 43 There has been much work done in the field of cement science that seeks to optimize cement composition, improve cement hydration rates, and in turn lower the carbon footprint of global cement use. [44][45][46]…”
Section: Cyclizationmentioning
confidence: 99%
“…It is also worth noting that in addition to zeolites, calcium silicates also play an important role in the composition of Portland cement, and thus have significant environmental impact. 43 There has been much work done in the field of cement science that seeks to optimize cement composition, improve cement hydration rates, and in turn lower the carbon footprint of global cement use. [44][45][46]…”
Section: Cyclizationmentioning
confidence: 99%
“…At the same time the structure, elastic, and mechanic properties have been several reported by Ayuela and co-workers since a few years ago [5][6][7][8]. Other recent studies proposed the chemical structure of some cement clusters studied at the DFT level [9].…”
Section: Introductionmentioning
confidence: 62%
“…At the same time, it was found that the variation of temperature rise rate with time is different for backfill bodies at different concentrations. This is because the heat release rate of the cement hydration reaction is affected by both time and temperature: different temperatures of backfill bodies at the same time leads to different heat release rates, and then the subsequent temperature rise is different [41].…”
Section: Temperature Distributionmentioning
confidence: 99%